Separation of Water/Oil Emulsions by an Electrospun Copolyamide Mat Covered with a 2D Ti(3)C(2)T(x) MXene - Moghaddasi, AbdolAli (Materials (Basel), 2020)
Purpose: Copolyamide 6,10 (coPA) electrospun mats were covered with multilayered (ML) and single-layered (SL) MXene (Ti(3)C(2)T(x)) as a membrane for the separation of water/vegetable oil emulsions. Methods: Prepared membranes were characterized by atomic force microscopy (AFM), profilometry, the contact angle measurements of various liquids in air, and the underwater contact angle of vegetable oil. The separation efficiency was evaluated by measuring the UV transmittance of stock solutions compared to the UV transmittance of the filtrate. Results: The MXene coating onto coPA mats led to changes in the permeability, hydrophilicity, and roughness of the membranes and enhanced the separation efficiency of the water/vegetable oil emulsions containing 10, 100, and 1000 ppm of sunflower vegetable oil. It was found that membranes were highly oleophobic (>124°) under water, unlike in air, where the membranes showed high oleophobicity (<5°). The separation efficiency of water/oil emulsions for both types of covered membranes reached over 99%, with a surface coverage of 3.2 mg/cm(2) Ti(3)C(2)T(x) (for ML-Ti(3)C(2)T(x)) and 2.9 mg/cm(2) (for SL-Ti(3)C(2)T(x)). Conclusions: The separation efficiency was greater than 98% for membranes covered with 2.65 mg/cm(2) of ML-Ti(3)C(2)T(x), whereas the separation efficiency for membranes containing 1.89 and 0.77 mg/cm(2) was less than 90% for all studied emulsion concentrations.